2017
DOI: 10.1371/journal.pone.0171984
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Infant and Child Feeding Index (ICFI) and nutritional status of 6- to 35-month-old children in rural western China

Abstract: BackgroundThe objective of this study was to determine the relationship between the quality of feeding practices and children’s nutritional status in rural western China.MethodsA sample of 12,146 pairs of 6- to 35-month-old children and their mothers were recruited using stratified multistage cluster random sampling in rural western China. Quantile regression was used to analyze the relationship between the Infant and Child Feeding Index (ICFI) and children’s nutritional status.ResultsIn rural western China, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 14 publications
1
29
1
5
Order By: Relevance
“…Our finding of a positive association between ICFI and child HAZ is consistent with other studies that have investigated the relationship between a summary of child feeding practices and child HAZ in rural (32,34,50) and urban populations (13,51) . However, our result contrasts those of Ntab et al (52) who found no association between ICFI and child HAZ in rural Senegalese children (n= 500, age 12-42 months).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of a positive association between ICFI and child HAZ is consistent with other studies that have investigated the relationship between a summary of child feeding practices and child HAZ in rural (32,34,50) and urban populations (13,51) . However, our result contrasts those of Ntab et al (52) who found no association between ICFI and child HAZ in rural Senegalese children (n= 500, age 12-42 months).…”
Section: Discussionsupporting
confidence: 92%
“…10 Several studies have also demonstrated an association between complementary feeding practice which assessed by using the ICFI and linear growth of children aged 6-23 months. 5,10,19,21 A study from Burkina Faso, West Africa, showed that mean LAZ was significantly and positively related to ICFI tertiles in children aged 6-23 months. 19 In addition, a study in urban slums of Mumbai also confirmed this finding and showed a significant association between ICFI and LAZ.…”
Section: Discussionmentioning
confidence: 99%
“…A higher score indicates a better quality of eating practices, which mainly include breastfeeding, bottle feeding, food groups and food diversity . There is evidence that the ICFI score is positively correlated with infant nutritional status in underprivileged population groups . However, the use of the ICFI to measure the impact of an intervention programme on children's eating practices has only been reported by Zhang , with adaptations according to recommendations for Chinese children.…”
Section: Discussionmentioning
confidence: 99%